2016
DOI: 10.1007/s11356-016-7787-6
|View full text |Cite
|
Sign up to set email alerts
|

Elemental composition in feathers of a migratory passerine for differentiation of sex, age, and molting areas

Abstract: AcknowledgmentsThe authors would like to thank Tamás Weiszburg for the SEM/BSE measurements performed at the Department of Mineralogy and Geochemistry of Eötvös Loránd University.The assistance of Tamás Szigeti, MSc and Gergely Tarsoly, MSc provided in the microwaveassisted digestion of feathers is also appreciated. Keywords: breeding, elemental distribution, habitat, inductively coupled plasma mass spectrometry, laser ablation, migratory birds, rare earth elements.3 HighlightsAmong the 38 elements investigate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
9
2

Year Published

2017
2017
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(15 citation statements)
references
References 54 publications
4
9
2
Order By: Relevance
“…In spite of differences in elemental fingerprint between wintering and breeding areas, no significant difference in the concentration of any element was detected according to sex or to the sex by feather growth location interaction both in multivariate (Table 2 ) and univariate analyses (Table 3 ). These results are consistent with previous studies of different passerine species, including the northern cardinals Cardinalis cardinalis and the great crested flycatchers Myiarchus crinitus (Cooper et al 2017 ), the collared flycatcher (Óvári et al 2018 ) and the Italian sparrow (Innangi et al 2019 ), reporting that sex-specific differences were not observed for different trace elements accumulated in feathers. The lack of sex-specific differences in the elemental fingerprint of barn swallow feathers suggests that the bioaccumulation rates of trace elements are consistent between both the sexes (Cooper et al 2017 ), probably because males and females use the habitats and exploit the same diet in both wintering and breeding areas (Møller 1994 ; Turner 2006 ; Liechti et al 2015 ).…”
Section: Resultssupporting
confidence: 92%
See 3 more Smart Citations
“…In spite of differences in elemental fingerprint between wintering and breeding areas, no significant difference in the concentration of any element was detected according to sex or to the sex by feather growth location interaction both in multivariate (Table 2 ) and univariate analyses (Table 3 ). These results are consistent with previous studies of different passerine species, including the northern cardinals Cardinalis cardinalis and the great crested flycatchers Myiarchus crinitus (Cooper et al 2017 ), the collared flycatcher (Óvári et al 2018 ) and the Italian sparrow (Innangi et al 2019 ), reporting that sex-specific differences were not observed for different trace elements accumulated in feathers. The lack of sex-specific differences in the elemental fingerprint of barn swallow feathers suggests that the bioaccumulation rates of trace elements are consistent between both the sexes (Cooper et al 2017 ), probably because males and females use the habitats and exploit the same diet in both wintering and breeding areas (Møller 1994 ; Turner 2006 ; Liechti et al 2015 ).…”
Section: Resultssupporting
confidence: 92%
“…The average concentration of trace elements accumulated in tail feathers of barn swallows decreased as follows: Al > Fe > Zn > Cu > Mn > Ni > Pb > Hg > Se > Cr > As > Cd. The levels and the elemental fingerprint observed in the present study were similar to those measured in feathers of diverse passerine species breeding in other geographical areas, including great tits Parus major from Belgium (Veerle et al 2004 ), collared flycatchers from Hungary (Óvári et al 2018 ), sand martins from different European breeding areas (Vallner et al 2000 ,; Szép et al 2003 ) and Italian sparrows Passer italiae from southern Italy (Innangi et al 2019 ), while they differed compared to those measured in tail feathers collected from house sparrows Passer domesticus living in southern Africa (Baker et al 2017 ). The toxic elements included in the priority list of contaminants of 2013/39/EU directive for surface water, namely Cd, Hg, Ni and Pb, were above the detection limit in all samples, with the exception of Cd.…”
Section: Resultssupporting
confidence: 84%
See 2 more Smart Citations
“…Here we apply a different technique to estimate dispersal among dialects: comparison of the trace element composition of feathers. This method has been used to track movements in several species of birds (Kelsall & Burton, 1979;Szép et al, 2003;Donovan et al, 2006;Gómez-Díaz & González-Solís, 2007;Norris et al, 2007;Óvári et al, 2016). Trace elements differ from stable isotopes in that they do not vary in a predictable pattern across the landscape, but depend on local features (Adout et al, 2007).…”
Section: Introductionmentioning
confidence: 99%